Foreign Investor Flows and Sovereign Bond Yields in Advanced Economies - Arslanalp, Serkan (IMF Working Papers; Working Paper, 2014)
Asset allocation decisions of international investors are at the core of capital flows. This paper explores the impact of these decisions on long-term government bond yields, using a quarterly investor base dataset for 22 advanced economies over 2004-2012. We find that a one percentage point increase in the share of government debt held by foreign investors can explain a 6-10 basis point reduction in long-term sovereign bond yields over the sample period. Accordingly, international flows to core advanced economy bond markets over 2008-12 are estimated to have reduced 10-year government bond yields by 40-65 basis points in Germany, 20-30 basis points in the U.K., and 35-60 basis points in the U.S. In contrast, foreign outflows are estimated to have raised 10-year government bond yields by 40-70 basis points in Italy and 110-180 basis points in Spain during the same period. Our results suggest that the divergence in long-term bond yields between core and periphery economies in the euro area may continue unless the 'normalization' of macroeconomic determinants of bond yields is accompanied by a similar 'normalization' of the foreign investor base.